Is Mindfulness Linked to Life Satisfaction? Testing Savoring Positive Experiences and Gratitude as Mediators - Cheung, Rebecca Y. M.; Lau, Elsa Ngar-Sze (Frontiers in Psychology, 2021)
Grounded in Mindfulness-to-Meaning Theory, this study examined the relation between dispositional mindfulness and life satisfaction through mediating mechanisms including savoring positive experiences and gratitude. A total of 133 Chinese mindfulness practitioners at 20–72 years old were recruited from a 3-day transnational meditation event in Hong Kong. Findings based on structural equation modeling indicated that controlling for sex, age, education, family income, number of hours of mindfulness practice per week, and type of administration, dispositional mindfulness was associated with satisfaction with life through savoring positive experiences and gratitude as mediators. The findings provided initial evidence for these processes between mindfulness and life satisfaction in the Chinese context. To promote life satisfaction, researchers and mental health practitioners should recognize the chain of mechanisms related to mindfulness.